KUALITAS STRATEGI BERSAING MEMEDIASI PENGALAMAN, PENGETAHUAN, DAN ADAPTABILITAS LINGKUNGAN TERHADAP KINERJA - Oxyopida, Farkhan; Sabihaini, Sabihaini; Darpito, Surpiko Hapsoro (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
This study aims to examine the effect of business experience, business knowledge, adaptability of the business environment to business performance, with the quality of the business strategy as a moderate variable. Hypothesis testing is carried out to test the effect of each independent variable on the dependent variable and test whether there is a mediating effect through the business strategy excellence variable. The population in this study were all the managers of the SMEs in the Pottery Industry in Kasongan. The research sample was selected using a purposive sampling technique. The research data was collected through a questionnaire with a survey method and analyzed using the Structural Equation Modeling (SEM) approach with an analysis tool using SmartPls Ver. 3.2.8. The results of this research can be concluded that there are three variables that have a positive and direct effect on business performance, namely business experience, business environment adaptability, and strategy quality while business knowledge only has a positive effect, but not significantly on business performance. hypothesis test results from the mediation relationship, business strategy quality mediates the variables business experience, business knowledge, and adaptability of the business environment to business performance.